The Role of English Language in Communication: Multidisciplinary Perspectives - Madhuben Punjabhai Galchar (Emerging Trends in Languages, 2026)
The English language performs an essential role in communication, serving as the universal medium through which people exchange data, express feelings, and build relationships. This research explores the importance of language in communication, examining its role in human interactions, the dynamics of effective communication, and the socio-cultural impact of language. Communication is a skill that involves a systematic and continuous process of speaking, listening, and understanding. We are also taught some communication skills directly through training, by bringing those skills into practice and getting them evaluated. The face of cutting-edge India has changed extensively due to globalization; it has delivered exceptional cultures to India. In modern-day global competition, no company needs to stay local; their goal is to expand all around the world. The paper addresses the research problem of understanding how English language shapes perceptions, influences behavior, and acts as a vehicle for social cohesion and relationships. Through a systematic review of literature and empirical research, the study evaluates the complex relationship between language and communication, highlighting its significance in diverse social, cultural, and professional contexts. Because you are seeking a paragraph-style summary, I have synthesized those multidisciplinary perspectives into a cohesive narrative. This format is ideal for academic submissions or introductory chapters. The English language has transcended its origins as a national tongue to become the primary global lingua franca, functioning as a crucial conduit for change in an increasingly globalized world. This paper adopts a multidisciplinary perspective to analyze how English allows communication across diverse sectors, moving beyond simple linguistics to explore its sociopolitical, economic, and technological dimensions. By examining the shift from “standard English” to the pluralistic concept of global English, the study highlights how the language now serves as a democratic tool for identity expression and cross-cultural mediation, instead of a rigid set of colonial rules. Ultimately, this research paper argues that the role of English in contemporary communication is characterized by adaptability and hybridization. As English continues to merge with local languages to form new hybrids, it reinforces its role not as a static entity, but as a fluid, evolving system. Understanding the multidisciplinary effect of English is vital for navigating the complexities of 21st-century international relations, schooling, and virtual interplay, necessitating a balanced method that promotes worldwide connectivity without sacrificing various linguistic diversity. The findings reveal that effective language use enhances interpersonal relationships, facilitates learning, and contributes to societal development.
Keywords: Language; communication; interpersonal relationships; language dynamics; multidisciplinary communication; powerful communique; social concord; socio-cultural impact